(untitled) (Bangladesh Medical Journal, 2016)
This cross sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka from January to December 2009, to determine the proportion of cortex and medulla of the ovary in di_erent age group of Bangladeshi women. This study was based on collection of 140 ovaries of 70 unclaimed female dead bodies from the morgue of Dhaka Medical College, Dhaka. The samples were divided into three age-groups including A (10-13 years), B (14-45 years) & C (46-52 years). Histological slides were prepared by using routine haematoxylin and eosin stain. Ten best prepared histological slides from each age group were examined to determine the thickness of the cortex and medulla & proportion of the thickness of the cortex and the medulla of the ovary were expressed in percentages. The mean proportion of the cortex and the medulla of the right ovary were found 80.83±0.58% and 19.17±0.58% in group A, 86.95±1.14% and 13.05±1.14% in group B, 70.53±1.53% and 29.47±1.53% in group C respectively. The mean proportion of the cortex and the medulla of the left ovary were found 80.63±0.58% and 19.37±0.58% in group A, 86.78±1.14% and 13.22±1.14% in group B, 70.41±1.50% and 29.59±1.50% in group C respectively. The difference in mean proportion of the cortex and the medulla was not signi_cant in between the ovaries. However, the difference in mean proportion of the cortex and the medulla of the ovary between group A & group B, group A & group C and group B & group C were statistically significant. Bangladesh Med J. 2015 Jan; 44 (1): 8-10